Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 172024 by Mikenice last updated on 23/Jun/22

let α and β be the root of the equation  ax^2 +bx+c=0. find the equation whose roots  are ((1/α)+(1/β)) and ((1/α)−(1/β))

letαandβbetherootoftheequationax2+bx+c=0.findtheequationwhoserootsare(1α+1β)and(1α1β)

Answered by Rasheed.Sindhi last updated on 23/Jun/22

Given equation:  ax^2 +bx+c=0  α+β=−(b/a) , αβ=(c/a),α−β=((√(b^2 −4ac))/a)  Required equation:  Sum of the roots=((1/α)+(1/β))+((1/α)−(1/β))         =((α+β)/(αβ))+((−(α−β))/(αβ))  =(((−b/a)−((√(b^2 −4ac)) )/a)/((c/a)))=((−b−(√(b^2 −4ac)) )/c)  Product of roots=((1/α)+(1/β))((1/α)−(1/β))      = (1/α^2 )−(1/β^2 )=((−(α+β)(α−β))/((αβ)^2 ))      =((−(−b/a)(−b−(√(b^2 −4ac)) /c))/((c/a)^2 ))     =−((ab)/c^3 )(b+(√(b^2 −4ac)) )   x^2 −(Sum of the roots)x+(product of the roots)=0  x^2 −(((−b−(√(b^2 −4ac)) )/c))x−((ab)/c^3 )(b+(√(b^2 −4ac)) )=0  c^3 x^2 +c^2 (b+(√(b^2 −4ac)) )x−ab(b+(√(b^2 −4ac)) )=0

Givenequation:ax2+bx+c=0α+β=ba,αβ=ca,αβ=b24acaRequiredequation:Sumoftheroots=(1α+1β)+(1α1β)=α+βαβ+(αβ)αβ=(b/a)(b24ac)/a(c/a)=bb24accProductofroots=(1α+1β)(1α1β)=1α21β2=(α+β)(αβ)(αβ)2=(b/a)(bb24ac/c)(c/a)2=abc3(b+b24ac)x2(Sumoftheroots)x+(productoftheroots)=0x2(bb24acc)xabc3(b+b24ac)=0c3x2+c2(b+b24ac)xab(b+b24ac)=0

Commented by Mikenice last updated on 23/Jun/22

thanks sir

thankssir

Commented by peter frank last updated on 23/Jun/22

thanks

thanks

Terms of Service

Privacy Policy

Contact: info@tinkutara.com